Agreement, dependencies, and Surface Correspondence in Obolo and beyond - Bennett, William G (Stellenbosch Papers in Linguistics Plus)
Obolo, a lower cross-river language spoken in the Niger Delta, exhibits an implicational dependency between the onset and coda of a syllable: if a syllable has a nasal onset, then it cannot also have an oral coda (Faraclas 1984, Rowland-Oke 2003). Vowel nasalisation facts reveal this to be a long-distance, consonant-to-consonant interaction. Vowels are predictably nasalised before a nasal consonant, but not after one, so the ban on disharmonic NVT syllables cannot be attributed to incremental local spreading of nasality to attain a long-distance result. The analysis proposed here explains the Obolo facts using the theory of Surface Correspondence (Rose and Walker 2004, Hansson 2010a, Bennett 2013) as similarity-driven agreement. Limits on this agreement prevent it from applying in certain conditions, which cause it to present as a one-way dependency rather than full bidirectional agreement. These limitations fall out from pre‑existing concepts in the harmony literature, namely position control and value dominance. The combination of these two effects in the same harmony system can serve to derive certain implicational dependencies from the same mechanism as agreement. This approach seems quite generalisable, as this paper demonstrates by applying it to a long-distance voicing dependency in Afrikaans (Coetzee 2014), in which root-medial voiced obstruents may not occur when this would produce disagreement with a voiceless root-initial obstruent.